Impact measurement and tracking in a climate context. Curriculum for a self-paced learning program - Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report presents a curriculum for an e-learning programme that is set to be a game-changer, offering agribusinesses a structured collection of expert-led insights, practical tools, and real-world applications to help them effectively measure, track, and communicate their impact. Whether you are an expert looking to contribute to the Masterclass’s development, a researcher eager to engage with practical tools, or an agribusiness seeking to enhance your impact measurement capabilities, this report offers valuable insights. Let’s dive into the exciting offerings by exploring the curriculum presented in the following pages.